A review of the New Caledonian Arpactophilus (Hymenoptera: Crabronidae) - Breitkreuz, Laura C.v.; Ohl, Michael; Engel, Michael S. (Zootaxa, 2016)
The diverse and unique fauna of the apoid wasp genus Arpactophilus Smith (Pemphredoninae: Stigmini: Spilomenina) occurring in New Caledonia is reviewed. The previously documented diversity of 17 species is expanded to a total of 48, with 31 new species described and figured from across the main island. The new species proposed here are: Arpactophilus arha, A. arhoe, A. bwatoo, A. caac, A. cemuhi, A. drehu, A. drubea, A. fagauvea, A. futuna, A. fwai, A. haveke, A. iaai, A. jawe, A. kumak, A. merle, A. nemi, A. nengone, A. nere, A. numee, A. nyelayu, A. orowe, A. paici, A. pije, A. pwaamei, A. pwapwa, A. tayo, A. tiri, A. vamale, A. xaracuu, A. xaragure, and A. yuanga, spp. nov. Diagnoses are provided for those previously described species and a key to the fauna presented, although six species are considered of uncertain identity: A. arboreus Bohart, A. dolichocara Bohart, A. kraussi Bohart, A. nemoralis Bohart, A. nigripes Bohart, and A. sylvaticus Bohart. Brief comments are made regarding the unique species radiation occurring in New Caledonia and the potential for future discoveries in the systematics and biology of Australasian Arpactophilus.